2016
DOI: 10.1074/mcp.m116.061333
|View full text |Cite
|
Sign up to set email alerts
|

Human Sirtuin 2 Localization, Transient Interactions, and Impact on the Proteome Point to Its Role in Intracellular Trafficking

Abstract: Human sirtuin 2 (SIRT2) is an NAD-dependent deacetylase that primarily functions in the cytoplasm, where it can regulate α-tubulin acetylation levels. SIRT2 is linked to cancer progression, neurodegeneration, and infection with bacteria or viruses. However, the current knowledge about its interactions and the means through which it exerts its functions has remained limited. Here, we aimed to gain a better understanding of its cellular functions by characterizing SIRT2 subcellular localization, the identity and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 106 publications
(118 reference statements)
6
19
0
Order By: Relevance
“…Then, we further locked five candidates that may serve as SIRT2 targets in AD progression by informatics analysis and finally identified RTN4 as the most impressive candidate for that it may interact with BACE1 (He et al, 2004; Murayama et al, 2006). Besides, a previous study that using metabolic labeling quantitative MS also suggested that RTN4 may transiently target SIRT2 (Budayeva & Cristea, 2016), and this possible interaction was also identified in other proteomic studies (Huttlin et al, 2015), supporting our results. RTN4, also known as Nogo, is one member of the RTN family and has mainly three isoforms (RTN4A, RTN4B, RTN4C), which are abundant in the nervous system (Chen et al, 2000).…”
Section: Discussionsupporting
confidence: 91%
“…Then, we further locked five candidates that may serve as SIRT2 targets in AD progression by informatics analysis and finally identified RTN4 as the most impressive candidate for that it may interact with BACE1 (He et al, 2004; Murayama et al, 2006). Besides, a previous study that using metabolic labeling quantitative MS also suggested that RTN4 may transiently target SIRT2 (Budayeva & Cristea, 2016), and this possible interaction was also identified in other proteomic studies (Huttlin et al, 2015), supporting our results. RTN4, also known as Nogo, is one member of the RTN family and has mainly three isoforms (RTN4A, RTN4B, RTN4C), which are abundant in the nervous system (Chen et al, 2000).…”
Section: Discussionsupporting
confidence: 91%
“…2a ). SIRT2 appeared at a characteristic location probably corresponding to the ER–Golgi intermediate compartment 23 , and it was present at lower levels in axotomized MNs at 7 dpi with respect to the control (Fig. 2b ).…”
Section: Resultsmentioning
confidence: 93%
“…To gain further insight into the functional roles of the newly identified SIRT2 interactors, gene ontology term enrichment analysis was performed using PANTHER 21 . The most enriched GO terms for biological processes included tricarboxylic acid cycle 22 , vesicle-mediated transport 8 and fatty acid catabolic processes 23 (Table S2). These are consistent with the growing body of reports which implicate SIRT2 as a key regulator of metabolic processes within the cell 7 .…”
Section: Resultsmentioning
confidence: 99%